Questioning of Discretion in the Regime of Constitutional Preliminary Injunctions in Ecuador - Coloma Gaibor, Alfredo Sebastián (USFQ Law Review, 2020)
An uncomfortable reality, but openly accepted reality is that Latin American justice systems are far from being efficient. Ecuador is not the exception. And it is not that justice cannot be obtained from the State, but society has convinced itself that it may take time to arrive. Mechanisms such as precautionary measures seek to resolve this difficulty related to the delay in the processes resulting from the congestion of the jurisdictional services. In the legal environment, the answer to a problem can be the cause of many others, as a consequence of a legislation plagued with antinomies that can lead the subject of rights to a state of defenselessness. This is the reason why this article seeks to be an exposition of the pertinent regulations to the case, in order to lead the reader to a well-founded discussion about the ethical and legal implications regarding precautionary measures. First, an account of the development of similar measures in Ecuador will be provided, then seeking to ground the weaknesses of the exposed regulations, resolution 2015-10509 will be used. As this case is a health-related issue, specifically dialysis procedures, a review of the relevant legal regime will clarify how precautionary measures are connected to fundamental rights. Subsequently, the scope of the laws that regulate this guarantee will be retaken and the risk that the discretion that triggers possible abuses of the law will be evidenced, after which it opens the way to criticism and observation that the Ecuadorian legal regime, regarding this chapter, seems to mitigate its rigor. The sensitivity of the issue lies in the powers of an institution that allows the generation of prohibitions or forcing certain actions with direct impact on citizens without having a trial procedure involved.